A riddle of culprit only vs multivessel or immediate vs staged revascularization in patients with non-ST elevation acute coronary syndrome: A meta-analysis - Yudi Her Oktaviono; Jannatin Nisa Arnindita; Pandit Bagus Tri Saputra; Nabilah Azzah Putri Wairooy; Arlia Ayu Damayanti; Suryo Ardi Hutomo; Nando Reza Pratama; Makhyan Jibril Al Farabi; Faisal Yusuf Ashari (PLoS ONE, 2025)
Background Percutaneous coronary intervention (PCI) is a revolutionary breakthrough in saving many lives from myocardial infarction. However, little is known about the PCI strategy in multivessel disease (MVD) Non-ST Elevation Acute Coronary Syndrome (NSTE-ACS) patients. Should complete revascularization be achieved or culprit-only is sufficient, then when the appropriate time of multivessel revascularization is, whether it is staged or immediate. Limited evidence is available on this matter compared to ST-elevation myocardial infarction (STEMI), even though NSTE-ACS patients carry poorer long-term prognoses compared to STEMI. Methods A thorough search for appropriate studies was executed across PubMed, Embase, Medline, Science Direct, and Scopus databases until July 4th, 2023. The risk ratio (RR) underwent analysis through Review Manager 5.4. Results Twenty-six studies with 222,350 MVD NSTE-ACS patients were included. Culprit-only revascularization was significantly related to a higher risk of non-fatal MI (RR: 1.41, 95% CI: 1.04-1.91, p = 0.03, I2: 65%) and all-repeat revascularization (RR 1.86, 95% CI 1.07-3.25, p = 0.03). While multistage multivessel revascularization was related to significantly higher all-cause mortality (RR: 1.73; 95% CI 1.43-2.10; p < 0.01; I2: 0%), TVR repeat (RR 1.38 95% CI 1.11-1.73, I2 =  18%, p = 0.004), and non-TVR repeat (RR 2.59; 95% CI 1,56-4.30; p = 0.0002; I2: 70%). Conclusion Patients with MVD NSTE-ACS treated with multivessel revascularization showed more favorable results than culprit-only. One-stage multivessel revascularization resulted in fewer adverse events than multistage. Additionally, a comprehensive and methodical prospective investigation is required to validate the factors accountable for these outcomes.